Rolling back democracy in the late Soeharto era: some implications for Indonesia's political culture - Chalmers, Ian (1997)
On 27 July 1996 Indonesian politics was shaken by the most widespread riots to occur in the capital city for over twenty years. The leader of the opposition Indonesian Democratic Party (PDI), Megawati Sukarnoputri, had recently been overthrown from within her party in a government-engineered move. When she refused to bow to pressure and her supporters continued to occupy the PDI headquarters in central Jakarta, her opponents mounted a violent assault, and were actively aided by local sections of the Armed Forces. The forced removal of a popular opposition figure by state-backed armed thugs, leading to perhaps dozens of deaths, caused outrage to spill onto the streets. Crowds of youth and other protestors blocked roads, burned buildings, hurled stones at anyone in uniform, and for the following day played cat-and-mouse with the security forces sent to quell unrest.